Effects of pile fermentation on the physicochemical, functional, and biological properties of tea polysaccharides. (1st June 2023) - Li, Qian; Liu, Lu; Zhang, Jiahan; Dong, Mingyu; Wang, Lan; Julian McClements, David; Fu, Yinxin; Han, Lingyu; Shen, Peiyi; Chen, Xiaoqiang
Graphical abstract: Highlights: TPS from sun-dried green tea and dark tea were extracted and analyzed. Physicochemical and structural property of TPS was changed after pile fermentation. Pile fermentation markedly enhance the functional and biological property of TPS. Abstract: This study investigated the influence of pile fermentation on the physicochemical, functional, and biological properties of tea polysaccharides (TPS). Results indicated that the extraction yield, uronic acid content, and polyphenol content of TPS greatly increased from 1.8, 13.1 and 6.3 % to 4.1, 27.9, and 7.8 %, respectively, but the molecular weight markedly decreased from 153.7 to 76.0 kDa after pile fermentation. Additionally, the interfacial, emulsion formation, and emulsion stabilization properties of TPS were significantly improved after pile fermentation. For instance, 1.0 wt% TPS isolated from dark tea (D-TPS) can fabricate 8.0 wt% MCT oil-in-water nanoemulsion ( d32 ≈ 159 nm) with potent storage stability. Moreover, the antioxidant and α-glucosidase inhibitory activities of D-TPS was higher than that of TPS isolated from sun-dried raw tea (R-TPS). Overall, this study indicated that pile fermentation markedly affected the physicochemical and structural characteristics of TPS, thereby improving their functional and biological properties.